Is endoscopic sphincterotomy beneficial for the treatment of acute gallstone pancreatitis with small bile duct stone?. Issue 2 (February 2019) - Kim, Sung Bum; Nam, Yoon Jeong; Kim, Kook Hyun; Kim, Tae Nyeun
Abstract : Background: Acute gallstone pancreatitis occurs when a gallstone is impacted at the ampulla of Vater. The role of endoscopic retrograde cholangiopancreatography in the treatment of small choledocholithiasis in these patients is uncertain. The aim of this study was to compare outcomes of expectant management with endoscopic sphincterotomy for the treatment of small choledocholithiasis (⩽5 mm) in patients with acute gallstone pancreatitis. Patients and methods: Of the 258 patients admitted for acute gallstone pancreatitis from January 2010 to December 2014, 174 patients with small choledocholithiasis were reviewed retrospectively. Patients with coexisting acute cholangitis and/or pancreatobiliary malignancy were excluded. They were divided into an endoscopic sphincterotomy group ( n =64) and an expectant management group ( n =110). Severity index and outcomes of pancreatitis, complications, and overall mortality were compared. Results: Age and sex were not significantly different between the two groups. The mean Ranson, acute physiology and chronic health evaluation-II, and bedside index of severity in acute pancreatitis scores were not significantly different between the two groups. The computed tomography severity index score was significantly higher in the expectant management group than in the endoscopic sphincterotomy group (1.6±1.1 vs. 1.0±0.9, P <0.001). Duration of hospitalization, time for normalization of the white blood cell count, and time for oral feeding were similar in both groups. There was no significant difference between two groups in the incidence of development of pseudocyst or walled-off necrosis. In addition, no difference was observed in the rate of recurrence of acute pancreatitis and readmission because of recurrent choledocholithiasis. Conclusion: Expectant management seems to be effective for the treatment of patients with acute gallstone pancreatitis and size of bile duct stones equal to or less than 5 mm.